IDENTIFICATION OF CULTURAL TOURISM ATTRACTIONS OF SEKADAU HILIR DISTRICT, SEKADAU REGENCY - Erni, Yuniarti (Fakultas Teknik Universitas Tanjungpura, 2022)
Tourism is one of the important sectors in the development of Indonesia, especially in cultural attractions. Cultural heritage tourism in Sekadau Regency, West Kalimantan Province consists of 4 tours, 2 of which are located in the center of the district capital, namely Lawang Kuari Cave and King of Sekadau Tomb. Both tours are potential historical sites to be developed as ODTW (Objects and Tourist Attractions) in Sekadau Regency. The cultural attractions of Sekadau Hilir District have problems in the form of unregulated cultural attractions to the characteristics of the district. The data analysis method used is qualitative descriptive analysis, which is reviewed based on variables: attraction, facilities, support, and additional services. Based on the results of identification, known that ODTW culture in Sekadau Hilir District consists of (1) art, (2) a livelihood system, (3) cultural tourism festivals, (4) palaces, and (5) sites, buildings, and historical monuments. The driving factor for the development of cultural tourism is the availability of cultural attractions that can attract tourists, both from the tourist of internal and outside the area. Inhibiting factors in the development of cultural tourism are lack of promotion, lack of availability of infrastructure and tourism support facilities, and inadequate human resources.